Case Study of Implementation Compresses (Allium Cepa L.) to Reduce Fever in Toddlers Post DPT Immunization - Heni Heryani; Lusi Lestari (Genius Journal, 2023)
Objective: The purpose of this study was to determine the effect of shallot comresses on redukcing fever in childern under five after DPT immunization. Method: The method used is a Qualitative method with a single case studi approach. The study was conducted on toddlers immunized by DTP who had a fever in the Utama Village. Toddlers with a fever are given shallot compresses on the armpits for 15 minutes, and then their body temperature is measured   Result: The study's results on a 7-month-old girl toddler, at 08.00 WIB on July 7, 2022, were given DPT exercise and had a fever with a body temperature of 38.40C. First, a compress is given to the toddler's armpit for 15 minutes. After that, a re-evaluation was carried out; with the measurement results, there was a decrease in body temperature to 37.10C. Conclusion: Onion compresses can reduce fever in toddlers after DPT immunization. This can be used as alternative midwifery care to deal with the side effects of DPT immunization.